STUDI EKSPLORATIF TINGKAT KEPUASAN PASIEN TERHADAP PELAYANAN KESEHATAN DI RUANGAN RAWAT GABUNG RSUP DR. M.DJAMIL PADANG TAHUN 2018 - Dian Furwasyih (JURNAL KESEHATAN MERCUSUAR, 2019)
Abstract In the last 2 (two) decades, coverage of deliveries in health facilities has increased; however, the decline in maternal and newborn mortality was remain slow. With the increase in the number of deliveries in health facilities, the attention of health workers is turning to the quality of services, because poor service quality contributes to maternal and infant morbidity and mortality (World Health Organization (WHO), 2016). Service quality has a very strong significant relationship with patient satisfaction. (Juliana, 2017). The aim of the study was to explore the level of patient satisfaction in the maternity room of Dr. M. Djamil Padang in 2018. The scope of the research was the process indicators. The research design was a cross-sectional study with qualitative methods. The informants were 71 people. The sampling technique is convenient sampling. Data collection was conducted from February 1 to March 31, 2018 with in-depth interview techniques. Data collection is assisted by 2 (two) interviewers. Each interview takes ± 12 minutes and was recorded using a mobile phone. Interviews were conducted in Indonesian. Data analysis with NVIVO QSR 10 application. The results showed that almost 30% of informants were between 31-35 years old, more than half (50.75%) of informants with secondary education, a small proportion of informants (16.42%) were working mothers, and more than 80% of informants were treated for more than 5 days. In the analysis of the level of patient satisfaction with the service obtained more than half (71.64%) informants expressed satisfaction with the services of health workers in the room. Nearly 16% of informants stated that they were not satisfied with the services received in the room. Suggestions for improvement focus on the attitude of officers when providing services, comfort during care, providing care information, and responding to the patient's complaints. There is a need for follow-up from the hospital regarding suggestions for these improvements to enhance the quality of services in the room. Keywords : patient satisfaction, maternity room, healthcare services